Comparative Evaluation of Biological Activity of Fraction Below 5 kDa from Cattle Cord Blood After Low-Temperature Storage (at -80°C) or Lyophilization to Treat Burn Wounds in Rats - Gulevskyy, Oleksandr; Moiseyeva, Natalia; Gorina, Olga; Nikolchenko, Andriy; Schenyavsky, Ivan (Problems of Cryobiology and Cryomedicine, 2020)
Biological activity of the low molecular weight (down to 5 kDa) fraction from cattle cord blood after storage in lyophilized state at 4°C and -80°C in the form of solution in a model of thermal burn of rats' skin was investigated. Actovegin with a pronounced wound healing activity was used as a comparator drug. The storage of low molecular weight fraction for 3 months under the chosen conditions was found not to reduce its biological activity. Introduced and lyophilized cord blood fraction to experimental animals after simulation of thermal skin burns contributed to a reduced burn wound area, normalization of leukocyte content and phagocytic activity of neutrophils in peripheral blood. The findings enable considering the lyophilization of the low molecular weight fraction followed by storage at 4°C as sensibly more expedient option of storing and transporting the biologically active substance. Probl Cryobiol Cryomed 2020; 30(1): 47-57